2004
DOI: 10.1111/j.1354-523x.2003.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Artefacts in oral incisional biopsies in general dental practice: a pathology audit

Abstract: The elicited clinical knowledge, the quality of the samples sent to the pathologists seem to suggest the advisability for the GDPs to perform diagnostic biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
0
51
0
2
Order By: Relevance
“…This is reassuring and suggests that GDPs are as capable of obtaining biopsies as their hospital colleagues, hence supporting the view that all dental practitioners possess sufficient skill to remove and submit tissue to a pathologist. 7 Only 17 cases were classified as artefacts which precluded diagnosis, compared with four cases from hospital staff. An artefact refers to an alteration to the surgical specimen, as a result of extraneous factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reassuring and suggests that GDPs are as capable of obtaining biopsies as their hospital colleagues, hence supporting the view that all dental practitioners possess sufficient skill to remove and submit tissue to a pathologist. 7 Only 17 cases were classified as artefacts which precluded diagnosis, compared with four cases from hospital staff. An artefact refers to an alteration to the surgical specimen, as a result of extraneous factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 This can occur at any time during the procedure including surgical, fixation and preparation artefacts. Seoane et al 7 reported that over 64% of specimens submitted by GDPs finding was the single case of a deposit of metastatic breast tumour in a male patient previously reported by one of us 8 and a case of non Hodgkin's lymphoma which were submitted as periapical granulomas. The discovery of unsuspected pathology in specimens reinforces the importance and need to submit all surgically removed tissue for histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is important to emphasize that both clinical and pathologic findings contribute to the accuracy of final diagnosis 40 . Initiatives such as the clinical referral guidelines proposed by Seoane et al 6 are recommended to improve diagnostic skills and potentially improve the early detection and treatment of several diseases, including oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies often occur between clinical impressions and histopathological diagnoses, with the latter considered the gold standard of oral mucosal lesions diagnosis 5,6,7,8 . In part, these discrepancies result from methodological differences in the criteria used for diagnosis and the professional performing the evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation